2017
DOI: 10.1128/aem.00734-17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genomic Characterization of Escherichia coli O157:H7 in Cow-Calf Herds throughout California

Abstract: Escherichia coli serotype O157:H7 is a zoonotic food-and waterborne bacterial pathogen that causes a high hospitalization rate and can cause lifethreatening complications. Increasingly, E. coli O157:H7 infections appear to originate from fresh produce. Ruminants, such as cattle, are a prominent reservoir of E. coli O157:H7 in the United States. California is one of the most agriculturally productive regions in the world for fresh produce, beef, and milk. The close proximity of fresh produce and cattle presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
1
12
2
Order By: Relevance
“…Surprisingly, large-herd farms had significantly lower odds of C. difficile recovery as compared to farms with fewer swine. This association is contradictory to associations commonly found between farm herd-size and the prevalence of other highly studied enteric pathogens (e.g., Salmonella, Campylobacter, Escherichia coli O157:H7) (Adesiyun et al, 2014;Guerin et al, 2007;Worley et al, 2017). It may be that the swine farms in this study with larger herds had more stringent hygiene and biosecurity protocols in place or greater worker adherence to such protocols than those with smaller herds.…”
Section: Discussioncontrasting
confidence: 91%
“…Surprisingly, large-herd farms had significantly lower odds of C. difficile recovery as compared to farms with fewer swine. This association is contradictory to associations commonly found between farm herd-size and the prevalence of other highly studied enteric pathogens (e.g., Salmonella, Campylobacter, Escherichia coli O157:H7) (Adesiyun et al, 2014;Guerin et al, 2007;Worley et al, 2017). It may be that the swine farms in this study with larger herds had more stringent hygiene and biosecurity protocols in place or greater worker adherence to such protocols than those with smaller herds.…”
Section: Discussioncontrasting
confidence: 91%
“…Particularly, the clade 8 is more likely to be associated with the severe disease cases. These results were quite different from those reported recently by our group based on a survey that involved 20 cattle farms from various regions in California, which revealed that the clade 8 was the most dominant group [ 51 ], probably reflecting certain geographic effects on the E . coli O157:H7 lineage distribution, as our current strains were from a feedlot located in the South Western region of the US.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding has been reflected in other studies, where STEC strains isolated from calves from the same pen showed low variability, indicating frequent within-pen transmission ( 28 ). Unique STEC O157 lineages also proliferated among cattle on US dairy farms with a high STEC O157 prevalence ( 29 ). SNP analysis indicated that STEC O157 populations on a farm were dominated by a single clonal type, but differences occurred between farms, and some clonal types were still present during resampling 11 months later ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unique STEC O157 lineages also proliferated among cattle on US dairy farms with a high STEC O157 prevalence ( 29 ). SNP analysis indicated that STEC O157 populations on a farm were dominated by a single clonal type, but differences occurred between farms, and some clonal types were still present during resampling 11 months later ( 29 ). Pulsed-field gel electrophoresis (PFGE) analysis of O26:H11 isolates ( n = 11) on three Australian farms also found unique strains at each farm ( 30 ).…”
Section: Discussionmentioning
confidence: 99%